2018
DOI: 10.1136/bjsports-2017-098968
|View full text |Cite
|
Sign up to set email alerts
|

Environmental, behavioural and multicomponent interventions to reduce adults' sitting time: a systematic review and meta-analysis

Abstract: ObjectiveTo examine the overall effectiveness of interventions for reducing adult sedentary behaviour and to directly compare environmental, behavioural and multicomponent interventions.DesignIntervention systematic review with meta-analysis.Data sourcesOvid PsycINFO, Ovid MEDLINE, EBSCOHost CINAHL, EBSCOHost SPORTDiscus and PubMed were searched from inception to 26 July 2017.Eligibility criteriaTrials including randomised controlled trials, quasi-randomised, cluster-randomised, parallel group, prepost, factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 62 publications
(233 reference statements)
5
46
0
5
Order By: Relevance
“…Our findings are supported by previous systematic reviews in adults [23,27,29,30], demonstrating that the interventions had a positive effect on reducing SB. In line with the findings from Peachey et al which included studies published up to July 2017 [27], the findings from this review demonstrated the greatest reduction in sitting time from environmental interventions. These findings are interesting considering that the global complexity scores in environmental interventions were considerably lower than that of behavioural and mixed interventions.…”
Section: Adult Interventionssupporting
confidence: 89%
See 3 more Smart Citations
“…Our findings are supported by previous systematic reviews in adults [23,27,29,30], demonstrating that the interventions had a positive effect on reducing SB. In line with the findings from Peachey et al which included studies published up to July 2017 [27], the findings from this review demonstrated the greatest reduction in sitting time from environmental interventions. These findings are interesting considering that the global complexity scores in environmental interventions were considerably lower than that of behavioural and mixed interventions.…”
Section: Adult Interventionssupporting
confidence: 89%
“…They found significant associations with sitting-to-standing reallocations included small-to-medium reductions in fasting plasma glucose (2%), triglycerides (11%) and total/HDLcholesterol ratio (6%) while sitting-to-stepping reallocations were significantly associated with medium reductions in body mass index (11%), waist circumference (7.5cm), triglycerides (14%) and two-hour plasma glucose (11%) [193]. Despite the comparatively smaller reductions in SB time found in our review, these changes in SB could still have a clinically meaningful impact on adult's health as a 30-minute per day reduction in daily sitting time has been suggested as an effective target for observing long-term health benefits in another systematic review [27].…”
Section: Adult Interventionsmentioning
confidence: 59%
See 2 more Smart Citations
“…Sedentary behaviours have been shown to be amenable to change in the general population, with a recent meta-analysis showing a reduction in daily sitting time of 30 minutes/day [13]. However, evidence from stroke survivors is limited and inconclusive with one Canadian home-based feasibility study (single group, N=34) showing promising findings in relation to a reduction in sedentary time post intervention [14], and one community-based Australian phase II pilot randomised controlled trial (N=35) demonstrating it is safe and feasible to intervene [15].…”
Section: Introductionmentioning
confidence: 99%